Report of the CARICOM/UNICEF Consultation on Health and Family Life Education, Barbados, 19-20 April, 1996 - (:unkn) unknown (My University, 1996)
As part of the CARICOM Multi-Agency Project on Health and Family Life Education (HFLE), a consultation was held with Chief Medical Officers and Chief Education Officers in the region. The report covers the areas addressed at the consultation: 1) Issues affecting youth, 2) Achievements and gaps in HFLE programmes in the region, and 3) HFLE programmes for the 21st century.
Keywords: health and family life education; HFLE; youth issues